(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The emergence of microfinance, a variety of progress was expected in the world within low-income households will be having permanent access to a range of good quality financial services to finance their income generating activities. Microfinance institutions preserve a check on the loan occupied by women and its convenience. But due to social standards or Indian male-controlled structure, male gained advantage in the family and take more benefits of loans are exhausted by the man of the house. The study highlighted on economic empowerment of women. Social empowerment mentions mostly for the social alert and literacy rate, specifically of women who are most demoralized in various parts of the emerging countries.